IMPACT OF INDUCED BENZALKONIUM CHLORIDE ON BIOCHEMICAL PARAMETERS AND BEHAVIORAL RESPONSES IN FRESHWATER FISH CYPRINUS CARPIO[L.] - Devika Rani H K; Parimala B (Chelonian Research Foundation, 2025)
The widespread use of household and industrial chemicals has led to significant environmental changes, particularly in aquatic habitats. This study examines the effects of Benzalkonium chloride, a popular floor cleaner, on freshwater fish's gills and muscle tissues, specifically Cyprinus carpio (L.). Fingerlings of C. carpio (average weight: 4.3±1.4 g; length: 5.1±1.7 cm) were sourced from the Turvekere fish farm in Tumkur, Karnataka. We conducted static bioassay tests to evaluate the acute toxicity of Benzalkonium chloride, exposing ten acclimatized fish to different concentrations to establish 24-hour LC50 values. We monitored behavioral changes and mortality rates every two hours while assessing alterations in biochemical parameters, such as glucose, glycogen, and protein levels in the gills and muscle tissues. The results showed that, relative to control groups, exposure to sub-lethal concentrations of Benzalkonium chloride led to significant decreases in glycogen and protein levels in both tissues, while glucose levels increased. The decline in glycogen may suggest a stress response involving increased metabolic activity. In contrast, the reduction in protein levels could stem from the utilization of amino acids for energy under stress. These findings underscore the heightened susceptibility of juvenile Cyprinus carpio to chemical pollutants, enhancing our understanding of the ecological impacts of household cleaning products on sensitive aquatic species during early developmental stages.